(untitled) (Chittagong University Journal of Biological Sciences, 2013)
The foodborne Listeria denitrificans was isolated from degraded rice and studied as an amylase producer. This microorganism showed maximum amylase production at temperature 27 ºC and medium pH 7.0, and on 3rd day during incubation period. Maximum amylase production by the isolate was found in medium containing 3.0 % starch as carbon source and 0.50 % yeast extract as nitrogen source. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13388 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):73-81, 2009